Strengthening the HR Capabilities – A Pathway to Strategic Success at SMEs of Punjab - Sharma, Manoj K.; Sharma, Sonali (Gyan Management Journal, 2023)
The Indian business sector is hyper-competitive and subject to the complexities of its environment. Operating in a highly digitalized and globalized world is not easy. However, by trying to strengthen its capabilities, a firm can face the challenges of a borderless world and other external pressures. Of all the internal factors, human resource (HR) is supreme. It is a firm’s most valuable asset and a major source for gaining competitive edge. Therefore, understanding its role in a firm’s strategic success in imperative. The present study attempted to determine the impact of HR practices on effective strategy implementation of small and medium enterprises (SMEs) of Punjab. Data was collected from 157 units through a self administered questionnaire. It was analyzed through mean scores, frequencies and multiple regression analysis. Results revealed that six of eight select HR practices had a statistically significant, strong and positive impact on strategy implementation. HR remuneration and rewards had the highest impact. The study concluded that adoption of positive HR practices like attractive remuneration packages, better training programmes, employee involvement and empowerment, etc. enhanced effectiveness of strategic actions. The findings are to benefit several parties and add Indian SME sector evidence to the domain.